Assessment of Casuarina equisetifolia Forst., Provenance Trial (inland) Taken up in Andhra Pradesh - Rao, P. S.; Rao, G. Maheswara; Venkaiah, K.; Satyanarayana, V. V. V. (Indian Forester, 2001)
The International Provenance trial of Casuarina equisetifolia was established in 1996, with 27 provenances in Regional Forest Research Centre, Rajahmundry, East Godavari District, Andhra Pradesh. The Australian Tree Seed Centre of CSIRO, Canberra, Australia coordinated in collection of seed throughout the natural range as well as from land race populations of Casuarina. The Analyses of Variance of data indicated significant difference among provenances for height, GGL, GBH and straightness a p=0.05level of significance, while axis persistence has showed no significant difference. Genetic analyses showed heritability estimates for the characters axis persistence and straightness (below 15%) while moderate estimates of heritability for height, GGL and GBH (between 40.60%). It is suggested that selections could be made from superior trees of individual provenances in order to have broad base for genetic improvement of Casllarina equisetifolia in Andhra Pradesh.